Analisis Implementasi Model Pentahelix sebagai Strategi Kolaboratif dalam Pengembangan Wisata Religi Dumai Islamic Center, Pemerintah Kota Dumai, Provinsi Riau - Siti Inne Mentari; Ferry Adhi Dharma (Universitas Tribhuwana Tungga Dewi, 2025)
This study aims to analyze the communication strategy of the Dumai City Government in developing the Dumai Islamic Center (DIC) as a religious tourism destination. Using qualitative methods with non-participant observation techniques, in-depth interviews, and documentation, data were analyzed through the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The results of the study indicate that the communication strategy utilizes print, electronic, and digital media and involves content creators to increase the visibility of DIC. The strength of this strategy lies in the attractiveness of DIC's architecture and extensive use of media, while its weaknesses are budget limitations and minimal involvement of academics. Opportunities arise from stakeholder involvement through activities such as bonsai exhibitions and bird singing competitions, while threats come from bureaucratic instability and competition from similar destinations. The final results of this study indicate that the application of the Pentahelix model through synergy between government, business, community, academics, and media is a strategic solution to ensure the sustainability of DIC's promotion and development as a leading religious tourism destination in Dumai City.Penelitian ini bertujuan untuk menganalisis strategi komunikasi Pemerintah Kota Dumai dalam mengembangkan Dumai Islamic Center (DIC) sebagai destinasi wisata religi. Menggunakan metode kualitatif dengan teknik observasi non-partisipan, wawancara mendalam, dan dokumentasi, data dianalisis melalui pendekatan SWOT (Strengths, Weaknesses, Opportunities, Threats). Hasil penelitian menunjukkan bahwa strategi komunikasi memanfaatkan media cetak, elektronik, dan digital serta melibatkan content creator untuk meningkatkan visibilitas DIC. Kekuatan strategi ini terletak pada daya tarik arsitektur DIC dan penggunaan media yang luas, sedangkan kelemahannya adalah keterbatasan anggaran dan minimnya keterlibatan akademisi. Peluang muncul dari keterlibatan pemangku kepentingan melalui kegiatan seperti pameran bonsai dan lomba kicau burung, sementara ancaman datang dari ketidakstabilan birokrasi dan persaingan destinasi serupa. Hasil akhir dari penelitian ini menunjukkan bahwa penerapan model Pentahelix melalui sinergi antara pemerintah, bisnis, komunitas, akademisi, dan media menjadi solusi strategis untuk memastikan keberlanjutan promosi dan pengembangan DIC sebagai destinasi wisata religi unggulan di Kota Dumai.